Dark Age Nunneries : The Ambiguous Identity of Female Monasticism, 800-1050 - Vanderputten, Steven (Book collections on Project MUSE., 2018)
In Dark Age Nunneries, Steven Vanderputten dismantles the common view of women religious between 800 and 1050 as disempowered or even disinterested witnesses to their own lives. It is based on a study of primary sources from forty female monastic ...